Vehicle tracking and accident detection system using accelerometer - Rani, B.; Praveen Sam, R.; Reddy Kamatam, Govardhan (International Journal of Engineering and Technology, 2018)
Nowadays road accidents are a major issue of concern. Even with so many modern devices present in the field of vehicle design, road lane design and heavy traffic control accidents do occur at a large scale. In most accidents, people lose their lives as no medical facility is reached there at proper time and place. To reduce this risk factor accident detection system leads important role. Any kind of accident detected is automatically sent as an alert to the required destination. Accident detection device installed in a vehicles when meets with an accident will send SMS/ messages to the pre-install numbers of the drivers family members, police station, ambulance and nearest hospital. This automated tracking system can be useful for tracking and detecting the exact position of any automobile, which has met with a collision by using Global Positioning System (GPS) and sensors.